Refactoring Assertion Roulette and Duplicate Assert test smells: a controlled experiment - Santana, Railana; Martins, Luana; Virgínio, Tássio; Soares, Larissa; Costa, Heitor; Machado, Ivan (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2022)
Test smells can reduce the developers' ability to interact with the test code. Refactoring test code offers a safe strategy to handle test smells. However, the manual refactoring activity is not a trivial process, and it is often tedious and error-prone. This study aims to evaluate RAIDE, a tool for automatic identification and refactoring of test smells. We present an empirical assessment of RAIDE, in which we analyzed its capability at refactoring Assertion Roulette and Duplicate Assert test smells and compared the results against both manual refactoring and a state-of-the-art approach. The results show that RAIDE provides a faster and more intuitive approach for handling test smells than using an automated tool for smells detection combined with manual refactoring.